If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -52 = 13x Solving -52 = 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -52 + -13x = 13x + -13x Combine like terms: 13x + -13x = 0 -52 + -13x = 0 Add '52' to each side of the equation. -52 + 52 + -13x = 0 + 52 Combine like terms: -52 + 52 = 0 0 + -13x = 0 + 52 -13x = 0 + 52 Combine like terms: 0 + 52 = 52 -13x = 52 Divide each side by '-13'. x = -4 Simplifying x = -4
| -10+6=x+4 | | 40-16=x-3 | | 6/2(2+1)=y | | 5(2x)=80 | | a+2+4=5 | | X^3-2x^2+2x-1=0 | | 5(x*2)=40/2 | | 1.1(1.25)+0.3=1.3+0.3(1.25) | | -9*x=x | | -1*x=x | | 2*x=x | | 6*x=x | | 4(6x)+2=15 | | -9(36-2x)=180 | | 20-12x=208 | | -6z+5=9-2z | | 20-12x=-203 | | 5z-z+2=6 | | 2z+6(z+3)=10 | | z=-1 | | 6-4w=-50 | | 6m+15= | | 7n-2=5n+10 | | 10w-24=-264-2w | | -70+8n=2(6n-95) | | -2v^2+v+3=0 | | -4a-6-44=-66 | | 8x^3-72a=0 | | -2v^2+v+2=0 | | 2v^2-v-2=0 | | 8-8x=84-22x | | 6w^2-11w+3=0 |